Ferromagnetic soft catheter robots for minimally invasive bioprinting - Cheng Zhou (Nature Portfolio, 2021)
Direct bioprinting in vivo has the potential to enable new clinical strategies but is currently limited by printing techniques. Here, the authors report on the development of a ferromagnetic soft catheter for magnetic computer controlled minimally invasive bioprinting and demonstrate the printing potential in vivo.